An image‐guidance system for dynamic dose calculation in prostate brachytherapy using ultrasound and fluoroscopy. Issue 9 (28th August 2014) - Kuo, Nathanael; Dehghan, Ehsan; Deguet, Anton; Mian, Omar Y.; Le, Yi; Burdette, E. Clif; Fichtinger, Gabor; Prince, Jerry L.; Song, Danny Y.; Lee, Junghoon
Abstract : Purpose: : Brachytherapy is a standard option of care for prostate cancer patients but may be improved by dynamic dose calculation based on localized seed positions. The American Brachytherapy Society states that the major current limitation of intraoperative treatment planning is the inability to localize the seeds in relation to the prostate. An image‐guidance system was therefore developed to localize seeds for dynamic dose calculation. Methods: : The proposed system is based on transrectal ultrasound (TRUS) and mobile C‐arm fluoroscopy, while using a simple fiducial with seed‐like markers to compute pose from the nonencoded C‐arm. Three or more fluoroscopic images and an ultrasound volume are acquired and processed by a pipeline of algorithms: (1) seed segmentation, (2) fiducial detection with pose estimation, (3) seed matching with reconstruction, and (4) fluoroscopy‐to‐TRUS registration. Results: : The system was evaluated on ten phantom cases, resulting in an overall mean error of 1.3 mm. The system was also tested on 37 patients and each algorithm was evaluated. Seed segmentation resulted in a 1% false negative rate and 2% false positive rate. Fiducial detection with pose estimation resulted in a 98% detection rate. Seed matching with reconstruction had a mean error of 0.4 mm. Fluoroscopy‐to‐TRUS registration had a mean error of 1.3 mm. Moreover, a comparison of dose calculations between the authors' intraoperative method and an independent postoperative method shows a small difference of 7% and 2% for D 90 and V 100, respectively. Finally, the system demonstrated the ability to detect cold spots and required a total processing time of approximately 1 min. Conclusions: : The proposed image‐guidance system is the first practical approach to dynamic dose calculation, outperforming earlier solutions in terms of robustness, ease of use, and functional completeness.